A new Luprops species from Western Ghats with redescriptions and identification key to the species of Indian Peninsula and Sri Lanka (Tenebrionidae: Lagriinae: Lupropini) - Sabu, Thomas K.; Merkl, Ottó; Abhitha, Prabhakar (Zootaxa, 2007)
Description of Luprops devagiriensis, sp. n. from montane evergreen forest (shola) in the southern region of Western Ghats, a global biodiversity hot spot in southwest India is given along with first report of L. rugosissimus Kaszab, 1980 outside Sri Lanka and redescriptions of L. tristis (Fabricius, 1801), L. curticollis Fairmaire, 1896 and L. gracilior Fairmaire, 1896. Notes on the habits of L. tristis Fabricius, a nuisance pest in residential buildings in the rubber belts of the south Indian state of Kerala and an identification key to the species from Indian Peninsula and Sri Lanka are provided.